The Effects of Manufacturer’s Prefit and Real-Ear Fitting on the Predicted Speech Perception of Children with Severe to Profound Hearing Loss - Quar, Tian Kar; Umat, Cila; Chew, Yong Yee (Journal of the American Academy of Audiology, 2019)
The use of probe microphone measures in hearing aid verification is often neglected or not fully used by practitioners. Some practitioners rely on simulated gain and output provided by manufacturer's fitting software to verify hearing aids.This study aims to evaluate the effectiveness of manufacturer’s prefit procedure in matching the prescribed real-ear targets. It also aims to study its correlated impact on the predicted speech perception in children with severe and profound hearing loss.This cross-sectional experiment was carried out by measuring the output of hearing aids based on prefit versus real-ear at low-, moderate-, and high-input levels. The predicted speech perception for different hearing aid fittings was determined based on the Speech Intelligibility Index (SII).Sixteen children (28 ears) aged between 4 and 7 yr, with severe to profound sensorineural hearing loss took part in the study.Two different types of hearing aids (Phonak and Unitron) were programmed based on their respective manufacturers’ Desired Sensation Levels (DSL) v5 Child procedure. The hearing aids were then verified using coupler-based measurements and individual real-ear-to-coupler differences. The prefit outputs were compared with the DSL v5 Child–prescribed outputs at low-, moderate-, and high-input levels. The hearing aids were then adjusted to closely match the prescribed output. The SIIs were calculated for the fittings before and after adjustment.Sixty four percent of fittings that were based on the prefit procedure achieved the optimal fit-to-targets, with less than 5-dB RMS deviations from the DSL v5 Child targets. After adjusting the hearing aids to attempt to meet the DSL v5 Child targets, 75% of the ears tested achieved the optimal fit-to-targets. On average, hearing aid outputs generated by the manufacturer’s prefit procedure had good and reasonable agreement with the DSL v5 Child–prescribed outputs at low- and mid-frequencies. Nonetheless, at 4000 Hz, the hearing aid output mostly fell below the DSL v5 Child–prescribed outputs. This was still the case even after the hearing aid was adjusted to attempt to match with the targets. At low input level, some prefit outputs were found to be higher than the prescribed outputs. The deviations of prefit outputs from the prescribed outputs were dependent on the type of hearing aid and input levels. There was no significant difference between the SII calculated for fittings based on the prefit and adjusted fit.Prefit procedure tends to produce outputs that were below the DSL v5 Child–prescribed outputs, with the largest mean difference at 4000 Hz. Even though the hearing aid gains were adjusted to attempt to match with the targets, the outputs were still below the targets. The limitations of hearing aids to match the DSL v5 Child targets at high-frequency region have resulted in no improvement in the children’s predicted speech perception.
Keywords: achieved gain; fit-to-targets; initial-fit; manufacturer fitting; prescribed gain; real-ear measures